Effects of clonal integration, nutrients and cadmium on growth of the aquatic macrophyte Pistia stratiotes. (9th October 2020) - Adomako, Michael Opoku; Alpert, Peter; Du, Dao-Lin; Yu, Fei-Hai
Abstract: Aims: Many wetlands are polluted with both nutrients and toxic metals and vegetated largely by clonal plants. We hypothesized that eutrophication and clonal integration can increase phytoremediation of toxic metal pollution by increasing plant growth, even under the stress imposed by toxicity. Methods: To test this hypothesis, single ramets of the common, widespread, floating, stoloniferous plant Pistia stratiotes L., were grown for 42 days at two levels of nutrient availability with and without 0.6 mg L −1 cadmium. Ramets were either severed from their vegetative offspring to prevent clonal integration or left connected, and severed offspring were either removed to eliminate intraclonal competition or left in place. Important Findings: Plants subjected to cadmium addition accumulated almost twice as much dry mass if given the higher nutrient level, due mainly to a doubling of the number of clonal offspring. Severance had little effect on the final mass of the parent plus offspring ramets. Removing offspring following severance had no effect on the final mass of the parental ramet in the presence of added cadmium, but it did increase the final mass of the parent in the absence of cadmium. These results support the hypothesis that eutrophication can increase remediation of toxic metal pollution by aquatic macrophytes but provided no evidence that clonal integration can affect remediation. Species such as P. stratiotes may help remediate co-pollution of wetlands with toxic metals and nutrients, and fragmentation of clones may not affect their remediation capacity.